Análise do viés atencional para faces em indivíduos depressivos e não depressivos utilizando o eyetracker - Figueiredo, Germano Rosa (2019)
Introduction: The current clinical assessment tools for mental health evaluation relies mostly on patient self-report, observation and judgment made by the professional. Recent studies suggest that mental disorders are correlated to attentional bias for visual information. It can be used to assess precise data on correlation with mental disorders. Objective: Compare durations of fixations on emotional faces during a free-viewing task between depressed and non-depressed individuals using eye-tracking technology. Method: Data of 69 participants (44 nondepressed and 25 depressed individuals) were analyzed. The experiment was based on a free-viewing task of pairs of faces, including 4 types of expressions: neutral, sad, happy and angry. All participants completed the Beck Depression Inventory-II (BDI-II) to assess the severity of depressive symptoms. The attention indexes were calculated by total eye events (fixations, saccades and blinks) durations throughout the experiment, total fixation durations during the presentation of emotional faces, ratio between total time of fixation during pairs of faces and total eye events durations during pairs of faces, total fixation duration on each faces and fixations outside the faces. Results: The results showed that depressed individuals had significantly lower values of fixation durations than the non-depressed individuals (p = 0.006 on happy faces; p = 0.034 on sad faces and p = 0.033 on angry faces). The eye events durations were also significantly different between the two groups (302.4 ± 41.2 - Depressed individuals, 331.5 ± 39.3 - Non-depressed individuals) (p = 0.005). The indices obtained from the comparison between BDI-II scores and fixation durations on facial expressions presented values with a statistically significant difference for happy faces (p = 0.033) among participants with severity of MINIMUM and SEVERE symptoms. Conclusion: The study showed that depressed individuals had decreased attentional bias for emotional faces and especially for happy faces. Significant differences were found for ocular events, with shorter times for depressed individuals. The use of eye-tracking provided accurate data for attentional bias analysis. The BDI-II was only useful to verify the severity of depressive symptoms, without correlation with attentional bias.